Auditoria externa em empresas que utilizam computador eletrônico: um estudo de casos - Baez Ibarra, Juan Ramon (1987)
The objective of this study was to investigate the relationship between the technical literature on EDP audit procedures and the procedures actually used by six public accounting firms in Brazil. We also tried to identify the difference between EDP auditing by brazilian public accounting firms and the foreign ones (Chapter I). In the litarature review, we present the current practices on external audit of companies that use complex computer systems and the future perspectives in this subject (Chapter I I ) . Then, we present the methodology used in the work and the rationale for its use in this kind of study (Chapter 111). Interviews using a questionary with open-ended questions, allowed us to have a description of audit procedures used by the audit firms in clients which use computer to process their transactions (Chapter IV). The results we have achieved allowed us to have analysis of EDP audit procedures used by the six public accounting firms shich participated in the research (Chapter V). Finally, we compare the results we have obtained to the existing literature, we present the conclusions, make our recommendations and suggest new studies (Chapter VI).